Synthesis and Characterization of Ball-Type Homo-Dinuclear Phthalocyanines with Four 4,4'-{Propane-1,3- Diylbis[Nitrilo(E)Methylyidene-2-Phenyleneoxy}Bridges - Evliyaoğlu, Merve; Yazıcı, Ayşegül (Fırat University, 2018)
In this study, Co2Pc2 2, Cu2Pc2 3, Ni2Pc2 4 and Zn2Pc2 5 were synthesized in two steps. In the fisrt step 4,4'- {propane-1,3-diylbis[nitrilo(E)methylyidene-2-phenyleneoxy} diphthalonitrile 1 was prepared by the nitro group displacement reaction of N,N-Bis(salicylidene)-1,3propanediamine compound with 4-nitrophthalonitrile compound (1:2) in dry DMF as the solvent, in the presence of K2CO3 as the base, at room temperature. In the second step the new ball-type metallo phthalocyanines were synthesized by the reaction of 1 and corresponding metal salts [Co(CH3COO)2, Cu(CH3COO)2, Ni(CH3COO)2 and Zn(CH3COO)2] (2:1) in the medium without solvent. The structure of the synthesized compounds were characterized using FT-IR, 1H-NMR and UV-VIS spectroscopy techniques.

Bu çalışmada, yeni top tipi metalli ftalosiyaninler;  Co2Pc2 2, Cu2Pc2 3, Ni2Pc2  4 ve  Zn2Pc2  5 iki basamakta sentezlendi. İlk basamakta 4,4'-{propan-1,3-diilbis[nitrilo(E)metiliden-2-fenilenoksi]} diftalonitril 1 bileşiği  N,N-bis(salisiliden)-1,3-propandiamin bileşiği ile 4-nitroftalonitril bileşiği (1:2) oranında, oda sıcaklığında,  çözücü olarak kuru DMF?de, baz olarak K2CO3 varlığında, nitro grubu yer değiştirme tepkimesi ile hazırlandı. İkinci basamakta yeni top tipi ftalosiyaninler; ilk basmakta sentezlenen 1 ve uygun metal tuzları ile (2:1) oranında [Co(CH3COO)2, Cu(CH3COO)2, Ni(CH3COO)2 ve  Zn(CH3COO)2] çözücüsüz ortamda sentezlendi. Sentezlenen bileşiklerin yapıları FT-IR, 1H-NMR ve UV-VIS spektroskopi teknikleri kullanılarak karakterize edildi.
Dört 4,4'-{Propan-1,3-Diilbis[Nitrilo(E)Metiliden-2-Fenilenoksi]}Köprülü Top-Tipi Homo-Dinükleer Ftalosiyaninlerin Sentezi ve Karakterizasyonu